From rookie to Rocky?: on modernity, identity and white-collar boxing - Wright, Edward John (2018)
This thesis is the first sociological examination of white-collar boxing in the UK; a form of the sport particular to late modernity. Given this, the first research question asked is: what is white-collar boxing in this context? Further research questions pertain to social divisions and identity. White-collar boxing originally takes its name from the high social class of its practitioners in the USA, something which is not found in this study. White-collar boxing in and through this research is identified as a practice with a highly misleading title, given that those involved are not primarily from white-collar backgrounds. Rather than signifying the social class of practitioner, white-collar boxing is understood to pertain to a form of the sport in which complete beginners participate in an eight-week boxing course, in order to compete in a publicly-held, full-contact boxing match in a glamorous location in front of a large crowd. It is, thus, a condensed reproduction of the long-term career of the professional boxer, commodified for consumption by others. These courses are understood by those involved to be free in monetary terms, and undertaken to raise money for charity. As is evidenced in this research, neither is straightforwardly the case, and white-collar boxing can, instead, be understood as a philanthrocapitalist arrangement. The study involves ethnographic observation and interviews at a boxing club in the Midlands, as well as public weigh-ins and fight nights, to explore the complex interrelationships amongst class, gender and ethnicity to reveal the negotiation of identity in late modernity.